2020
DOI: 10.1111/ecc.13204
|View full text |Cite
|
Sign up to set email alerts
|

The development of a family participatory dignity therapy programme for patients with haematologic neoplasms and their family caregivers in China: A feasibility study

Abstract: Objective To develop a communication prompt based on dignity therapy to facilitate effective conversations between patients with haematologic neoplasms and their family caregivers and to improve the programme and preliminarily explore the benefits and challenges of family participatory dignity therapy (FPDT). Methods A mixed‐methods approach was applied to develop and revise the programme. The FPDT was developed and validated using the Delphi survey, and its further improvement was explored with a simple one‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Our findings highlight the possible positive effects of family support for reducing the demoralization of palliative care patients. Palliative care professionals may focus on how they may help family members to better convey their support to patients with demoralization, like facilitating family members' developing meaningful interactions with patients via legacy activities (Allen et al, 2008;Allen, 2009) and involving family members' participation in activities which aim to enhance patients' dignity in end-of-life care (Wang et al, 2020). At the same time, palliative care professionals may also need to pay attention to supporting family caregivers of palliative care patients who may be influenced by patients' demoralization and are at risk of demoralization (Hudson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the possible positive effects of family support for reducing the demoralization of palliative care patients. Palliative care professionals may focus on how they may help family members to better convey their support to patients with demoralization, like facilitating family members' developing meaningful interactions with patients via legacy activities (Allen et al, 2008;Allen, 2009) and involving family members' participation in activities which aim to enhance patients' dignity in end-of-life care (Wang et al, 2020). At the same time, palliative care professionals may also need to pay attention to supporting family caregivers of palliative care patients who may be influenced by patients' demoralization and are at risk of demoralization (Hudson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More qualitative studies and integrated cultural adaptations are needed to revise DT. Related studies have probed into this aspect 39 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, psychological suffering is considered as a stigma due to gossip and judgements from others, resulting in poor acceptance of psychological interventions. Considering the distinctive cultural features, it is important for dignity therapists to take Chinese cultural characteristics into account when conducting DT with Chinese patients (Wang et al, 2020), such as using euphemistic expressions and avoiding taboo words to protect patients from feeling offended. In addition, patients with an implicit personality expressed superficially in answering DT questions because of Confucian introverted culture and low literacy in rural areas in mainland China (Sun & Qin, 2009); while DT benefits patients depending on the full outpouring of patients in the therapeutic process (Chochinov, 2002), therefore, how to guide patients to unburden themselves should be a critical part of DT training.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, applying other digital approaches, such as interviewing by videoconferencing or creating software‐generated e‐products, may allow for decreased time and cost (Bentley et al, 2020). Moreover, unexpected events such as sudden deterioration in health during DT implementation added more difficulties to therapists (Wang et al, 2020). Thus, it was suggested that dignity therapists need to get familiar with patients' health conditions with the help of the ward staff to identify the most appropriate time to conduct DT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation